Carbapenemase screening in an Irish tertiary referral hospital: Best practice, or can we do better?. Issue 4 (December 2020) - Fahy, S.; O'Connor, J.A.; O'Brien, D.; Fitzpatrick, L.; O'Connor, M.; Crowley, J.; Bernard, M.; Sleator, R.D.; Lucey, B.
Summary: Background: Carbapenems are a family of end line antibiotics with increasing levels of resistance that are a cause for concern. Aim: To ascertain whether the CPE screening programme employed in an acute tertiary hospital is fit for purpose. Method: We outlined the current working algorithm employed using a universal screening programme over a 26-month screening period. Rectal swabs are cultured on arrival. Those with suspicious growth are further investigated using NG-Carba 5 lateral flow tests and Vitek 2.0 sensitivity cards. These practices were compared with NHS guidelines. Findings & Conclusions: In all, 53 true positives were detected from 45 patients since the screening was implemented in early 2018 (46 OXA-48, 6 KPC, 1 NDM). As the rate of screening increased, the number of positive screens decreased over time. There were a lot of similarities between the HSE guidelines and the published NHS CPE toolkit. It was evident that there is no standard practice being employed across all hospitals. Comparing the MUH to national guidelines it appears to be quicker and more effective with universal screening in place at reducing the potential contacts and identifying carriers. Cost analysis indicates that the need to confirm all positive strains in a reference lab is costly, unnecessary and time consuming. There are adequate confirmatory tests available in-house for routine positive screens. It was concluded that infection prevention and control are key to identifying and controlling possible outbreaks in a hospital setting.